ChemInform Abstract: Towards Lignin‐Based Functional Materials in a Sustainable World. Issue 15 (24th March 2016) - Kai, Dan; Tan, Mein Jin; Chee, Pei Lin; Chua, Yun Khim; Yap, Yong Liang; Loh, Xian Jun
Abstract: Review: 178 refs.